FAKTOR-FAKTOR GEOPOLITIK YANG MEMPENGARUHI PERGERAKAN HARGA BITCOIN TAHUN 2022-2024 - Damayanti, Shinta; Muhith, Achmad Farhan (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study investigates the impact of geopolitical factors on Bitcoin price movements from 2022 to 2024. Employing a qualitative, explanatory approach, the research draws on secondary data from scholarly literature, official reports, and credible online sources. The analysis is grounded in the Geopolitical Risk theory, focusing on six indicators: armed conflict, foreign policy changes, international sanctions, regional tensions, terrorism threats, and diplomatic crises. Findings reveal that armed conflicts, particularly the Russia-Ukraine war and the Iran-Israel confrontation, had the most significant and immediate effect on Bitcoin prices, often triggering panic selling and market downturns. Other geopolitical events, such as U.S.-China tensions and international arrest warrants, produced less pronounced effects or even positive sentiment, depending on investor perceptions. Regulatory developments, such as the UK's crypto legislation, were associated with short-term price gains, suggesting geopolitical stability can enhance market confidence. The study concludes that while Bitcoin operates outside traditional financial systems, it remains highly sensitive to global geopolitical developments. Armed conflicts continue to be the primary driver of volatility, underscoring the importance of geopolitical awareness for investors and policymakers in the evolving digital asset landscape.